Last voyage of the Demeter - vredal, Andre 1973-; Schut, Bragi F.; Olkewicz, Zak, 1983-; Fischer, Bradley J.; Medavoy, Mike; Messer, Arnold W.; Hawkins, Corey, 1988-; Franciosi, Aisling, 1993-; Dastmalchian, David; Botet, Javier, 1977-; Cunningham, Liam; Briones, Jon Jon, 1965-; et al. (Universal City, CA Universal Studio Distribution Services, 2023)
Dracula's unholy presence dooms the crew of the merchant ship Demeter as it sails from Carpathia to London.
Based on the log of the Demeter from Bram Stoker's Dracula.
Originally produced as a motion picture in 2023.
Wide screen (2.39:1).
Bonus features: Altnernate opening; Deleted scenes; Commentary; From the pits of hell: Dracular reimagined; Evil is aboard: the making of The last voyage of the Demeter; Dracula & the digital age; Feature commentary with director Andre vredal and producer Bradley J. Fischer.
Director of photography, Tom Stern ; editor, Patrick Larsgaard ; music, Bear McCreary.
Corey Hawkins, Aisling Franciosi, David Dastmalchian, Javier Botet, Liam Cunningham, Jon Jon Briones, Chris Walley, Stefan Kapicic, Martin Furulund, Nikolai Nikolaeff, Woody Norman.
Keywords: Dracula -- Count (Fictitious character) -- Drama; Monsters -- Drama; Vampires -- Drama; Merchant ships -- Drama; Monster films; Vampire films; Horror films; Feature films; Fiction films; Film adaptations; Video recordings for the hearing impaired; Video recordings for people with visual disabilities